2021
DOI: 10.1590/1980-57642021dn15-010001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of older patients with COVID-19: a systematic review of case reports

Abstract: ABSTRACT. In the context of the current COVID-19 pandemic, higher morbidity and mortality have been reported in older adults. This age group presents physiological changes and its own clinical conditions such as frailty, dementia, among others. Objective: To describe the characteristics of COVID-19 patients, both over and under 80 years old, by conducting a systematic review of the literature describing case reports, and to summarize and critically assess these characteristics. Methods: Systematic review. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
(84 reference statements)
1
5
0
2
Order By: Relevance
“…In the systematic review by Tan et al 14 , critically ill patients with COVID-19 had an average age of 62.6 years. Our findings agree with the evidence found in several studies that pointed out a more significant occurrence of the critical form of the disease in older patients 15 - 19 . The decreased cardiopulmonary reserve in old patients increases the risk of complications, and the aging of the immune system (immunosenescence), leads to a pro-inflammatory trend, contributing to an exacerbated response to SARS-CoV-2 16 , 20 .…”
Section: Discussionsupporting
confidence: 93%
“…In the systematic review by Tan et al 14 , critically ill patients with COVID-19 had an average age of 62.6 years. Our findings agree with the evidence found in several studies that pointed out a more significant occurrence of the critical form of the disease in older patients 15 - 19 . The decreased cardiopulmonary reserve in old patients increases the risk of complications, and the aging of the immune system (immunosenescence), leads to a pro-inflammatory trend, contributing to an exacerbated response to SARS-CoV-2 16 , 20 .…”
Section: Discussionsupporting
confidence: 93%
“…17 However, a systematic review by Córdova et al . 16 revealed that age ≥ 80 years was consistent with progressive physiological changes and clinically relevant. We, therefore, did a further analysis using this cut-off and found that AS/MS-COVID patients aged ≥ 80 years were nearly 2 times more likely to develop SSIs than those aged 60-79 years (11/11 [or 100%] vs. 12/23 [or 52.2%]; P = 0.0058; 95% CI, 1.3 to 2.83; RR, 1.92).…”
Section: Discussionmentioning
confidence: 62%
“…They often have frailty, sarcopenia, disability, cognitive decline, anxiety, depression, and so on, promoting negative progression of the disease. 16 In this study, we followed the United Nation (UN)’s definition of older persons, which accepts the chronological age of 60 years as the cut-off value. 17 However, a systematic review by Córdova et al .…”
Section: Discussionmentioning
confidence: 99%
“…A imunossenescência, que é definida como a diminuição da função da imunidade inata e adquirida, aumenta a vulnerabilidade às doenças infectocontagiosas e associa-se a um desequilíbrio imunológico que predispõe a um estado pró-inflamatório crônico no organismo; essas alterações fisiológicas são alguns dos principais fatores que explicam a maior agressividade da infecção pelo SARS-CoV-2 em idosos (CÓRDOVA et al, 2021).…”
Section: Covid-19 Em Idosos: Mortalidade E Manifestações Clínicasunclassified
“…No que se refere às manifestações clínicas apresentadas pelos pacientes idosos acometidos pela COVID-19, as mesmas têm, a princípio, grande semelhança com os sintomas da população adulta em geral e incluem: febre, fadiga, tosse seca, ageusia, anosmia, entre outros; contudo, ressalta-se novamente que a propensão para a evolução para SRAG com necessidade de hospitalização é significativamente maior em pacientes idosos (CÓRDOVA et. al, 2021;PEREIRA, et.…”
Section: Covid-19 Em Idosos: Mortalidade E Manifestações Clínicasunclassified